The Relationship Between Abnormal Audit Fees and Future Stock Price Crash Risk: An Audit Quality Approach - Jalilzadeh Shirvani, Seyyed Amirreza (Business, Marketing, and Finance Open, 2027)
The present study aimed to investigate the relationship between abnormal audit fees and future stock price crash risk and to examine the moderating role of audit quality in this relationship among companies listed on the Tehran Stock Exchange. This study employed an applied, quantitative, and explanatory research design using panel data analysis. The statistical population consisted of all non-financial firms listed on the Tehran Stock Exchange during the period 2018–2024. After applying screening criteria, including continuous trading activity, availability of complete financial information, and consistency in fiscal year reporting, a final sample of 168 firms comprising 1,176 firm-year observations was selected. Data were collected from audited financial statements, annual reports, and stock market databases. Future stock price crash risk was measured using firm-specific crash-risk indicators derived from stock returns, while abnormal audit fees were estimated as the residual component of an audit fee expectation model. Audit quality was assessed using audit-related quality indicators, including auditor characteristics and reporting quality measures. Descriptive statistics, correlation analysis, and panel regression techniques were employed to test the study hypotheses. The F-Limer and Hausman tests were used to determine the appropriate panel estimation model, and robustness diagnostics were conducted to ensure the validity of the findings. The results revealed a significant positive relationship between abnormal audit fees and future stock price crash risk (β = 0.384, p < 0.001), indicating that firms paying unusually high audit fees were more likely to experience future stock price crashes. Audit quality exhibited a significant negative effect on crash risk (β = –0.296, p < 0.001), suggesting that higher-quality audits reduce the likelihood of extreme negative stock price movements. Furthermore, the interaction term between abnormal audit fees and audit quality was negative and statistically significant (β = –0.248, p < 0.001), demonstrating that audit quality weakens the positive association between abnormal audit fees and crash risk. The final moderated regression model explained 51.6% of the variance in future stock price crash risk and showed strong overall explanatory power. The findings suggest that abnormal audit fees constitute an important governance signal associated with increased future stock price crash risk. However, high audit quality mitigates this adverse effect by enhancing transparency, strengthening monitoring effectiveness, and reducing managerial incentives to conceal unfavorable information. The study highlights the critical role of auditing quality in protecting investors and promoting capital market stability. These results provide valuable implications for regulators, auditors, investors, and corporate boards seeking to improve financial reporting credibility and reduce information-related market risks.